Glucose‐induced incretin hormone release and insulin sensitivity are impaired in patients with idiopathic gastroparesis: results from a pilot descriptive study. Issue 8 (12th May 2013) - Prévost, G.; Ducrotté, P.; Cailleux, A.; Khalfi, K.; Basuyau, J. P.; Lefebvre, H.; Kuhn, J. M.
Abstract Background Incretin hormones [glucagon‐like peptide‐1 (GLP‐1) and glucose‐dependent insulinotropic peptide (GIP)] released by the gut modulate gastrointestinal motility and influence gastric emptying (GE). Abnormal secretion or sensitivity to these hormones could contribute to the pathogenesis of gastroparesis. The aim of this study was to investigate incretin hormone secretion during a prolonged oral glucose load in non‐diabetic patients with documented idiopathic gastroparesis. Methods Fifteen patients referred for digestive postprandial discomfort with delayed GE demonstrated by a 13C‐labeled octanoate breath test were included and compared with 10 healthy controls. A 75 g oral glucose load was performed, with blood samplings every 30 min for 5 h, to determine glucose, insulin, GIP, and GLP‐1 blood levels. Key Results Fasting GIP concentration was significantly higher in the patient group (56.1 ± 5.8 pg mL−1vs 29.9 ± 7.7 pg mL−1, P =0.012). Postglucose load GIP concentrations were also significantly elevated in patients with gastroparesis, whereas GLP‐1 concentrations during fasting and postglucose load conditions were not different to those of healthy controls. Moreover, glucose tolerance during glucose load was abnormal in patients, combining hyperglycemic insulin resistance and hyperinsulinism patterns, while fasting values for glycemia, insulin sensitivity, and insulin concentrations were normal. Conclusions & Inferences Patients with idiopathic gastroparesis exhibit abnormal GIP levels associated with impaired insulin sensitivity during oral glucose load. Further studies are needed to establish the involvement of these defects in the pathophysiology of gastroparesis.